High Performance Nano Device with Reduced Short Channel Effects in High Temperature Applications. (10th May 2017) - Zareiee, Meysam
Abstract : Solving the problem of short channel effects in Metal Oxide Semiconductor Field effect transistors is an important challenge of electronic industry. Moreover, self heating and hot carrier effects are major problems in the devices based on Silicon on Insulator technology. In this paper, a new structure is proposed to overcome the mentioned problems. So, a P + region is considered in bottom of the source region and is extended into the buried oxide region. Moreover, a HfO2 window is considered in border of source and channel region. This strategy helps to increase the device performance and obtain more reliable device. The proposed transistor is simulated using ATLAS simulator and the results shows that the proposed structure has acceptable behavior comparing to the conventional one.